Enhanced Solubilisation of Six PAHs by Three Synthetic Cyclodextrins for Remediation Applications: Molecular Modelling of the Inclusion Complexes - Morillo, Esmeralda; Sánchez-Trujillo, María Antonia; Moyano, José Ramón; Villaverde, Jaime; Gómez-Pantoja, María Eulalia; Pérez-Martínez, José Ignacio (PLOS ONE, 2012)
Solubilisation of six polycyclic aromatic hydrocarbons (PAHs) (acenaphthene, anthracene, fluoranthene, fluorene, phenanthrene and pyrene) by three synthetic cyclodextrins (CDs) (2-hydroxypropyl-β-CD, hydroxypropyl-γ-CD and ramdomly methylated-β-CD) was investigated in order to select the CD which presents the greatest increase in solubility and better complexation parameters for its use in contaminated scenarios. The presence of the three cyclodextrins greatly enhanced the apparent water solubility of all the PAHs through the formation of inclusion complexes of 1∶1 stoichiometry. Anthracene, fluoranthene, fluorene and phenanthrene clearly presented a higher solubility when β-CD derivatives were used, and especially the complexes with the ramdomly methylated-β-CD were favoured. On the contrary, pyrene presented its best solubility results when using 2-hydroxypropyl-γ-CD, but for acenaphthene the use of any of the three CDs gave the same results. Complementary to experimental phase-solubility studies, a more in-depth estimation of the inclusion process for the different complexes was carried out using molecular modelling in order to find a correlation between the degree of solubilisation and the fit of PAH molecules within the cavity of the different CDs and to know the predominant driving forces of the complexation.